Exploring the Customer Journey and Experience in the Digital Banking Era Through the Lens of Online Flow State - Sri Ismulyati; Maya Maria; Hubertina Karolina Ngarbingan; Ginta Ginting (AIBPM Publisher, 2025)
The rapid digitalization of banking services enhances transaction speed, security, and convenience; however, challenges persist in technology acceptance, regulatory readiness, and the optimization of Digital Customer Experience (DCX), particularly among younger consumers. This study develops and empirically tests a comprehensive model explaining the antecedents and consequences of DCX in digital banking. By integrating Information Integration Theory, Multi-Attribute Utility Theory, Value Co-Creation Theory, Attitude–Behavior Context Theory, and Flow Theory, the study proposes Online Flow State as a central mediating mechanism linking service attributes and behavioral outcomes. A quantitative approach was employed, with data collected from 214 young digital banking users in Jakarta and surrounding areas using purposive non-probability sampling. Structural Equation Modeling with Partial Least Squares (SEM-PLS) was applied for hypothesis testing. The results indicate that Awareness and Knowledge, Technology and Innovation, and User Interface significantly influence Online Flow State, which in turn strongly enhances DCX. Furthermore, DCX significantly increases Customer Loyalty both directly and indirectly through Value Co-Creation and Customer Engagement. However, Security and Ease of Use, as well as Speed, do not significantly affect Online Flow State. These findings underscore the importance of immersive digital experiences in fostering engagement and long-term loyalty